2016
DOI: 10.1021/acs.joc.6b00194
|View full text |Cite
|
Sign up to set email alerts
|

A Nitrogen-Assisted One-Pot Heteroaryl Ketone Synthesis from Carboxylic Acids and Heteroaryl Halides

Abstract: A practical and highly effective one-pot synthesis of versatile heteroaryl ketones directly from carboxylic acids and heteroaryl halides under mild conditions is reported. This method does not require derivatization of carboxylic acids (preparation of acid chlorides, Weinreb amides, etc.) or the use of any additives/catalysts. A wide substrate scope of carboxylic acids with high functional group tolerance has also been demonstrated. The results reveal that the presence of an α-nitrogen on the halide substrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…In agreement with the general notion in the literature, ,,,,, our exploratory studies (Table ) revealed that no addition of phenylmagnesium bromide ( 8a ) occurs to the sodium carboxylate ( Na-6a ; entry 1), and a similar result is obtained in the presence of PrNHLi ( 9b ; entry 2), probably due to the THF in the commercial Grignard solution . In stark contrast, i -Pr 2 NMgCl·LiCl ( 9a ) has a dramatic effect in enhancing the conversion and selectivity of the reaction, yielding ketone 1a as the major product (entry 3).…”
supporting
confidence: 89%
See 1 more Smart Citation
“…In agreement with the general notion in the literature, ,,,,, our exploratory studies (Table ) revealed that no addition of phenylmagnesium bromide ( 8a ) occurs to the sodium carboxylate ( Na-6a ; entry 1), and a similar result is obtained in the presence of PrNHLi ( 9b ; entry 2), probably due to the THF in the commercial Grignard solution . In stark contrast, i -Pr 2 NMgCl·LiCl ( 9a ) has a dramatic effect in enhancing the conversion and selectivity of the reaction, yielding ketone 1a as the major product (entry 3).…”
supporting
confidence: 89%
“…The addition of aromatic Grignard reagents to benzoates would give rise to important benzophenone compounds, but it is particularly problematic due to the lower reactivity of aromatic carboxylates and aryl Grignard reagents. To the best of our knowledge, this reaction has only been studied using chelate-assisted heteroaryl substrates or lithium propylamide as an additive (Scheme B) . However, the application of these processes in organic synthesis is severely limited by the narrow scope, and the inhibition in the presence of tetrahydrofuran, which is the most common solvent for synthesizing, storing, and distributing Grignard reagents. , Overcoming the challenges associated with the direct addition of Grignard nucleophiles ( 8 ) to carboxylate anions ( 6 ) is key to enabling an extended modular synthesis of ketones from CO 2 ( 3 ) .…”
mentioning
confidence: 99%
“…The polymer structures and synthetic routesa re depicted in Scheme1.T hree brominated benzoylpyridine derivatives 2benzoyl-5-bromopyridine (1), 2-(4-bromobenzoyl)pyridine (2), and 3-(4-bromobenzoyl)pyridine (3)a sa cceptor building blocks were obtained by the optimizeds ynthetic method. [64][65][66] The corresponding precursors 9,9-dihexal-10-(6-benzoylpyridin-3-yl)-9,10-dihydroacridine( A3PyB), 9,9-dihexal-10-(4-((pyridin-2yl)carbonyl)phenyl)-9,10-dihydroacridine (AB2Py), and 9,9-dihexal-10-(4-((pyridin-3-yl)carbonyl)phenyl)-9,10-dihydroacridine (AB3Py) were preparedf rom the Pd-catalyzed CÀNcoupling reaction of brominated benzoylpyridine and 9,9-dihexal-9,10-dihydroacridine with tBuONa as the base in excellent yield. Further bromination in the dark smoothly afforded almostq uantitative bromoacridine monomers M A3PyB ,M AB2Py ,a nd M AB3Py ,o f which the fluorescencew as dramatically weakenedr elative to their precursors.…”
Section: Resultsmentioning
confidence: 99%
“…Acids underwent deprotonation to give intermediate 20.1 , which led to coupling products 20.2 . The Zhu group developed the construction of 2‐pyridyl benzyl ketone 20.3 via a one‐pot reaction of i PrMgBr, i PrMgCl⋅LiCl and 2‐iodopyridine (Eq. 20‐2).…”
Section: Deprotonationmentioning
confidence: 99%